The Emerging of Japanese Neologism and Aging Society - Suartini, Ni Nengah (Universitas Pendidikan Indonesia (Indonesia University of Education), 2019)
Neologism are new words, terms or phrase created to apply to new concepts or to make older terminology sound more contemporary. The changing of society reflected in language is the emerging of myriads of neologisms. Japan currently is trying to cope with the aging population, known as aging society. The new words are invented to describe social phenomenon around the aging society in Japan. Considering the influence of social changing and neologisms, it is significant to learn how these new words are created. This study aimed to investigate issues concerning Japanese neologisms in aging society from the perspectives of characteristics, definition and social connotations. List of aging society neologisms is developed by looking in academic articles, scholarly books and online sources. The result shows that aging society neologisms created by combining existing words, borrowing, abbreviation and by rhyming with existing words or simply playing with sounds. Japanese aging society neologisms are the language mirror to reflect social phenomenon that the public concerns most. The study of neologisms is also a valuable tool to understand social cultural changes and improve communicative and cultural competence of the Japanese learners.